2015
DOI: 10.1007/s12031-015-0600-z
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PFTK1 Inhibits the Migration of Glioma Cells

Abstract: The prognosis of glioma patients is generally poor, so it is urgent to find out the underlying molecular mechanisms. PFTK1 is a member of cyclin-dependent kinases (Cdks) family and has been reported to contribute to tumor migration and invasion. In this study, we aimed to explore the expression and function in human glioma. Western blot and immunohistochemistry were used to evaluate the expression of PFTK1. PFTK1 expression was higher in glioma tissues compared with normal brain tissues, and its level was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…S6), and in previous study (21). CDK14 expression was also up-regulated in other cancers, including breast cancer and glioma (26,27). Furthermore, upregulated CDK14 was highly associated with the poor prognosis of patients with breast cancer (26), or HCC (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…S6), and in previous study (21). CDK14 expression was also up-regulated in other cancers, including breast cancer and glioma (26,27). Furthermore, upregulated CDK14 was highly associated with the poor prognosis of patients with breast cancer (26), or HCC (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, analyses of transposon insertion sites from a Sleeping Beauty (SB) transposon mutagenesis screen in a HBV-related HCC mouse model revealed a significant enrichment of common insert sites (CISs) in CDK14 gene (25). Second, previous studies have shown that the CDK14 abnormalities could affect cell growth, invasion, migration and motility in various cancers cell lines, including HCC (21,24,(26)(27)(28)(29). Third, CDK14 was shown to interact with cyclin Y to activate non-canonical Wnt signaling in HCC (29).…”
Section: Discussionmentioning
confidence: 99%
“…(64) The decreases in ATP probe uptake for BRAF and M4K5 in the BRAFi resistant 1205LuR cell line confirm the direct and off target inhibitory actions of vemurafenib, while CDK14 has been implicated in maintaining various hallmarks of cancer in several tumor types including ovarian, pancreatic, breast and gastric cancer as well as glioma. (65-69) Never in Mitosis Gene A (NIMA)-related protein kinase, NEK4, plays an important role in microtubule positioning and its deletion makes cancer cells either sensitive or resistant to microtubule poisons. (70) Apart from this, deletion of NEK4 was also found to delay replicative senescence and DNA damage repair in human fibroblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although cell cycle proteins have long been considered to be unable to influence the migration of cells, previous studies have demonstrated that PFTK1 protein either activated or was involved in Wnt signaling and promoted migration and invasion (16). A study has previously indicated that PFTK1 can modulate oligodendrocyte differentiation via the PI3K/AKT pathway (32), whereas downregulation of PFTK1 expression inhibited glioma cell migration (17). Based on these results, PFTK1 was considered to be a potent target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…PFTK1 is a novel member of the Cdc2-related serine/threonine protein kinases family, which can regulate the expression of cyclins and the cell cycle (13). Previous studies have demonstrated high expression of PFTK1 in several types of malignant tumor, including hepatocellular carcinoma (14), esophageal (11), breast (15) and gastric (16) cancers, as well as glioma (17). It is involved in cell cycle regulation, tumor proliferation, migration and invasion (18).…”
Section: Introductionmentioning
confidence: 99%